2013
DOI: 10.1021/ja408754z
|View full text |Cite
|
Sign up to set email alerts
|

Tubular Polymersomes: A Cross-Linker-Induced Shape Transformation

Abstract: Polymersomes, polymeric vesicles constructed of block copolymers, can undergo a sphere-to-tubule transition under the influence of a chemical modification of the polymeric bilayer. A strain-promoted alkyne-azide cycloaddition (SPAAC) reaction between azide handles inside the hydrophobic domain of the membrane and an excess of a bicyclo[6.1.0]nonyne (BCN)-cross-linker causes the vesicle to stretch in one dimension. Tubular polymersomes up to 2 μm in length can be obtained with this shape transformation. The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 23 publications
2
60
0
Order By: Relevance
“…The initial concentrations of PEG-PS before the addition of H 2 O was 3.33 mg ml −1 for sample1, 5 mg ml −1 for sample 2 and 10 mg ml −1 for sample 3. In this range, initially spherical polymersomes are formed232426. All samples turned cloudy when the amount of H 2 O reached 20%.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The initial concentrations of PEG-PS before the addition of H 2 O was 3.33 mg ml −1 for sample1, 5 mg ml −1 for sample 2 and 10 mg ml −1 for sample 3. In this range, initially spherical polymersomes are formed232426. All samples turned cloudy when the amount of H 2 O reached 20%.…”
Section: Methodsmentioning
confidence: 97%
“…We showed that spherical polymersomes, assembled from poly(ethylene glycol)-polystyrene (PEG-PS), deflate into cup-shaped polymersomes called stomatocytes232425. Rod-shaped polymersomes have been created by using crosslinkers26 or rehydration27. Bicontinuous cubic structures have been reported as well28.…”
mentioning
confidence: 99%
“…4147 In contrast, vesicle-to-worm or vesicle-to-sphere order–order transitions have been recently reported, which can also be used to trigger the on-demand release of encapsulated nanoparticle cargoes. 4851 These latter transitions are typically the result of a subtle reduction in the geometric packing parameter 52 arising from the responsive behavior of either the stabilizer block or the membrane-forming block toward an external stimulus such as temperature, 5357 pH, 5861 CO 2 , 62 cross-linker, 63 enzyme, 64 or redox. 65 In principle, vesicles that undergo morphological transitions after selectively binding to specific analytes (either by covalent bond formation or by host–guest supermolecular interactions) present in the external solution offer new strategies for targeted delivery and release applications.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, nanotubes (tubular polymersomes) are exciting candidates for the development of NVs due to their high aspect ratio and potential for immunotherapy, alongside drug delivery. Nanotubes have been engineered through chemical cross-linking using bio-orthogonal click chemistry [66] or polymer blending in a film rehydration process [67]. Recognising the importance of using biodegradable polymers in the design of materials for medical applications [68] we have recently developed a facile methodology for the generation of biodegradable nanotubes via the osmotically-induced elongation of PEG-polylactide polymersomes [69].…”
Section: Morphological Engineering Of Polymeric Nanostructuresmentioning
confidence: 99%